General and Genetic Toxicology of Enzyme-Treated Ginseng Extract Toxicology of Ginseng Rh2+ - Mi-Kyung Jeong; Chong-Kwan Cho; Hwa-Seung Yoo (Korean Pharmacopuncture Institute, 2016)
Objectives: Ginseng Rh2+ is enzyme-treated ginseng extract containing high amounts of converted ginsenosides, such as compound k, Rh2, Rg3, which have potent anticancer activity. We conducted general and genetic toxicity tests to evaluate the safety of ginseng Rh2+. Methods: An acute oral toxicity test was performed at a high-level dose of